Communication skills in basic training of physiotherapy students - Leonor Almeida Santos; Sílvia Queirós; Germano Couto; Rute Meneses (Instituto Politécnico de Viseu, 2022)
Introduction: The high relevance of clinical/healthcare communication as a vital skill in the provision of care and paramount in healthcare education determined the relevance of its teaching, and recommendations are to introduce it in undergraduate learning. Objetives: Identify, via expert consensus, the clinical/healthcare communication skills to be taught to physiotherapy students in their basic training (degree). Methods: An online questionnaire was implemented in a panel of experts in clinical/healthcare communication, following the Delphi technique until consensus was attained. Results: Twenty-seven clinical/healthcare communication skills were identified, of which 25 had a consensus of ≥80% in the ranking of the degree of importance, as well as the 10 most important to teach to physiotherapy students in terms of their basic training (degree). Conclusion: The study allowed the specification and listing of the central communication skills in pre-graduate training in physiotherapy, which may serve, in the future, as a proposal for new syllabuses in this area, as well as for the development of a curricular unit that cuts across the higher education physiotherapy degree courses in Portugal, seeking to equip future Portuguese physiotherapists with the same clinical/healthcare communication skills.